Sistem Informasi Pelaporan Perkembangan Pasien (SI-PELPASI) berbasis Mobile Android - Gea, Yusuf Abdul Aziz; Muhamad Alda (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The use of Android mobile applications in the healthcare sector as tools for patient progress reporting has become a significant innovation. The mobile Android-based patient progress reporting information system (SI-PELPASI) serves as a solution to enhance efficiency and accuracy in patient monitoring. This study aims to develop a mobile Android-based patient progress reporting information system at the Bukit doa rehabilitation centre, an Institution for Mandatory Reporting (IPWL). The system development in this study employs the System Development Life Cycle (SDLC) method, which consists of systematic stages: the planning stage aims to plan the system, the analysis stage involves reviewing existing and current systems and collecting data through interviews and observations, the design stage includes designing Unified Modelling Language (UML) diagrams and the user interface, the implementation stage uses the Kodular app creation platform, and the testing stage uses the black box method to test system functionality. Our findings resulted in the Patient Progress Reporting Information System in the form of a Mobile Android application named SI-PELPASI. The application runs smoothly and can be operated on Android-based mobile devices. With this application, the process of reporting patient progress becomes faster and real-time.